If f(1) = 3 and f(n) = f(n-1) + 3 then find the value of f(5).

Skip to content# If f(1) = 3 and f(n) = f(n-1) + 3 then find the value of f(5).

Mathematics ##
Comments (3) on “If f(1) = 3 and f(n) = f(n-1) + 3 then find the value of f(5).”

### Leave a Reply Cancel reply

If f(1) = 3 and f(n) = f(n-1) + 3 then find the value of f(5).

i believe the answer is 323 ft

step-by-step explanation:

[tex]Alarge asteroid crashed into a moon of another planet causing several boulders from the moon to be p[/tex]

the terms of a geometric sequence can be found by beginning with the first term and multiplying by the common ratio repeatedly. a recursive formula for a geometric sequence with common ratio r is given by an=ran−1 a n = r a n − 1 for n≥2 n ≥ 2 .

step-by-step explanation:

f(5) = 15

Step-by-step explanation:

f(2) = f(2-1) + 3

= f(1) + 3

= 3 + 3

= 6

f(3) = f(3-1) +3

= 6 + 3

= 9

f(4) = f (4-1) + 3

= 9 + 3

= 12

f(5) = f(5-1) + 3

= 12 + 3

= 15